2013
DOI: 10.1007/s11274-013-1517-8
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of thermostable β-galactosidase on epoxy support and its use for lactose hydrolysis and galactooligosaccharides biosynthesis

Abstract: Thermoresistant, recombinant β-galactosidase from Thermotoga maritima was purified and immobilized on the surface of epoxy-coated magnetic beads. The enzyme, which has hexameric quaternary structure as shown by gel filtration chromatography, attaches to the resin through multiple covalent linkages that involve different subunits. The bound enzyme shows higher stability than the free form. The immobilized enzyme showed to be efficient for the hydrolysis of lactose and the biosynthesis of galactooligosaccharides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 49 publications
2
38
0
2
Order By: Relevance
“…Covalent immobilization has the advantage of forming robust linkages between the enzyme and the carrier, which minimizes the loss of activity caused by enzyme leakage from the support [10], extends its lifetime by protecting the three-dimensional structure of the protein [11] and allows the development of continuous processes. The use of immobilized β-galactosidases in continuous bioreactors has mostly been applied to the hydrolysis of lactose in cheese whey [12][13][14].…”
Section: Immobilization Of β-Galactosidase From B Circulans On Glyoxmentioning
confidence: 99%
“…Covalent immobilization has the advantage of forming robust linkages between the enzyme and the carrier, which minimizes the loss of activity caused by enzyme leakage from the support [10], extends its lifetime by protecting the three-dimensional structure of the protein [11] and allows the development of continuous processes. The use of immobilized β-galactosidases in continuous bioreactors has mostly been applied to the hydrolysis of lactose in cheese whey [12][13][14].…”
Section: Immobilization Of β-Galactosidase From B Circulans On Glyoxmentioning
confidence: 99%
“…Therefore, new technologies have been developed for the production of milk products with low lactose content in order to satisfy the need for people suffering from lactose intolerance (Relpius, 2008). Different methods have recently been proposed in order to remove lactose from milk, as such lactose hydrolysis, capillary electrophoresis, ultrafiltration, and ion-exchange chromatography (Navarro et al, 2014;Bargeman, 2003;Marín-Navarro et al, 2014;Harju, 2007;Mohammad et al, 2012;Oliveira et al, 2014). Other studies have shown the feasibility of using the molecular recognition ability of molecularly imprinted polymers (MIPs) in processes such as adsorption using polymer or silica-based imprinted materials for proteins, polysaccharides and nucleic acids as templates (Li et al, 2014;Escobar and Santos, 2014;Dickert and Lieberzeit, 2006;Turner et al, 2006;Bossi et al, 2007;Bergmann and Peppas 2008;Kryscio and Peppas, 2012;Whitcombe et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Comparative docking analysis with a DA type 3 enzyme (TmLac) and a DA type 5 enzyme (BgaD-D) may add some hints about the structural basis for this different product specificity. Previous studies with TmLac showed that the main transglycosylation product of this enzyme is β-D-(1,3)-galactosyl-lactose, with a minor production of β-D-(1,6)-galactosyl-lactose [47]. Site-directed mutagenesis and structural modelling of TmLac suggested that Trp 959 (Fig 5B) functions as the aromatic binding platform for the acceptor lactose in the synthesis of the β-(1,3) GOS [4].…”
Section: Discussionmentioning
confidence: 99%